Risk Factors for Non-communicable Diseases in Vietnam: A Focus on Pesticides - Dang, Hoang V.; Nguyen, Luong T.; Tran, Ha T.; Nguyen, Huyen T.; Dang, Anh K.; Ly, Viet D.; Frazzoli, Chiara (Frontiers in Environmental Science, 2017)
Agent Orange, which was sprayed in southern Vietnam by the American government, was the main source of dioxin exposure in Vietnam. From the early 1990s, agriculture of Vietnam has attained advances under intensive cultivation. Both production and yields per crop has raised significantly at the farm level, but, on the other hand, the quantity of pesticides used in agriculture has been increased in the absence of regulations and good practices. Illegal business of pesticides with false labels, as well as marketing of expired or poor quality products in stores without license are so popular in Vietnam. Misuse and improper use in agriculture in Vietnam has led to a variety of problems, such as environment pollution (including food producing animals) and adverse health impact on animals and humans. Open dumpsites worsen the general scenario. Similar to the environmental exposure, human exposure to DDT in Vietnam was ranked among the highest worldwide, with recognized effects. Exposed communities have to face birth defects, health disorders and non-communicable diseases (NCDs), from metabolic syndrome, asthma, infertility and other reproductive disorders through to diabetes, obesity, cardiovascular and neurodegenerative diseases, and cancer. A common feature of many chronic disorders and NCDs is metabolic disruption: environmental chemical factors disturb cellular homeostasis, thus affecting the ability of the body to restore a functional internal environment. Among these, endocrine disrupting pesticides can interfere with the action of hormones including metabolic hormones, and are likely to represent the main concern for developmentally-induced NCDs. Since pesticides are often persistent and bio-accumulate in the food chain through the living environment of food-producing organisms, this paper discusses relevant aspects of risk assessment, risk communication and risk management.